Effectiveness of Blog Media to Increase Students' Short Story Writing Skill - Akhmad Sidiq (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Writing short story is a basic competency that is still taught in tenth grade NMC Vocational High School Malang. This research is based on the low ability of tenth grade NMC Vocational High School Malang in writing short story. This is because they are not used to expressing their feelings, thoughts, imagination, and are not able to connect between the imaginary world and the real world in short story. Besides that, the selection of strategies and media that is not appropriate in short story writing skills. Based on the obstacles experienced by students, researcher provided solutions to these problems with blog media to improve and develop short story writing skills for tenth grade NMC Vocational High School Malang. Blog media can improve the students’ short story writing skill because it gave ideas for the students to find and start short story writing activities. The results of the research that has been done show that there is an increase in writing short story. It can be proved by the improvement of student’s ability in the process and result of the students writing short story.